Response of Anther Donor Genotypes (F1) from Indica x Indica Crosses to Rice Anther Culture - Iswari Saraswati Dewi; Nuha Hera Putri; Bambang Sapta Purwoko (Jurnal AgroBiogen, 2019)
Anther culture is one of the in vitro techniques that can be used to accelerate the obtainment of purelines in the form of dihaploid (DH) plants resulted from androgenesis. The objectives of this research were to study response of anther donor genotypes in rice anther culture of F1 populations derived from indica x indica crosses and obtain spontaneous DH lines to be used further for variety development program. Anther donor plant used for the experiment consisted of four kinds of F1 populations derived from single crosses, i.e. IR85/I-5, BioR-81/I-5, Bio-R81/O18, and BioR-82/O-18. The result indicated that kindy of all F1 plants showed similar response to callus induction, but significatly different responses to plant regeneration. Genotypes of anther donor plants (F1) significantly affected the percentage of calli producing green plantlet, but not significantly affected the percentage of calli producing albino plantlet. Anther culturability of anther donor plants (F1) was relatively high, ranged from 2.0 to 7.0%. A total of 73 first generation of spontaneous DH lines (38.8%) from the grew out green plantlets was obtained from this study. The resulted DH lines are readily available to be selected and be used in rice cultivar development program.